Global kinetic hybrid simulation for radially expanding solar wind. Issue 8 (11th August 2017) - Dyadechkin, S.; Semenov, V. S.; Kallio, E.; Erkaev, N. V.; Alho, M.; Lammer, H.
Abstract: We present the results of a 1‐D global kinetic simulation of the solar wind in spherical coordinates without a magnetic field in the region from the Sun to the Earth's orbit. Protons are considered as particles while electrons are considered as a massless fluid, with a constant temperature, in order to study the relation between the hybrid and hydrodynamic solutions. It is shown that the strong electric field in the hybrid model accelerates the protons. Since the electric field in the model is related to electron pressure, each proton in the initial Maxwellian velocity distribution function moves under the same forces as in the classical Parker Solar wind model. The study shows that the hybrid model results in very similar velocity and number density distributions along the radial distance as in the Parker model. In the hybrid simulations, the proton temperature is decreased with distance in 1 order of magnitude. The effective polytropic index of the proton population slightly exceeds 1 at larger distances with the maximum value ∼1.15 in the region near the Sun. A highly non‐Maxwellian type of distribution function is initially formed. Further from the Sun, a narrow beam of the escaping protons is created which does not change much in later expansion. The results of our study indicates that already a nonmagnetized global hybrid model is capable of reproducing some fundamental features of the expanding solar wind shown in the Parker model and additional kinetic effects in the solar wind. Key Points: A new global kinetic hybrid model developed to investigate radially expanding solar wind The initially Maxwellian solar wind results in Parker's solar wind model type of acceleration The model can be used to analyze a non‐Maxwellian solar wind and dynamical events